Exercise Attenuates Doxorubicin-Induced Myocardial Injury by Inhibiting TSHR and Regulating Macrophage Polarization Through miR-30d-5p/GALNT7 - Haiyan Wu; Ruoyu Zhou; Hanxin Kong; Jieqiong Yang; Suijuan Liu; Xiaolin Wei; Kunzhi Li; Yunmei Zhang (Journal of Immunology Research)
Conclusion: EXE can modulate the miR-30d-5p/GALNT7 axis to inhibit the expression of TSHR, thereby regulating the polarization of macrophages to the M2 phenotype and ultimately alleviating DOX-induced myocardial injury, which provides new targets and strategies for the clinical treatment of myocardial injury.